Cultivating a Self-Study Community of Practice: Reflections of Faculty on Issues of Evolution and Functioning. Issue 2 (3rd May 2020) - Goodnough, Karen; Arnold, Christine; Azam, Saiqa; Maich, Kimberly; Moghaddam, Alireza; Penney, Sharon; Young, Gabrielle
ABSTRACT: Communities of practice, based on the work of Etienne Wenger, is being adopted as a framework in higher education to facilitate and foster professional learning. This article describes the emergence and cultivation of a university community of practice. Based on a desire to enhance our work as teacher educators and the learning experiences of our students, Karen, the first author, invited faculty to become part of a self-study group in a faculty of education. We remained a fluid entity for almost two years. Eventually, we evolved into a core group of seven faculty who were interested in conceptualizing and implementing a shared self-study inquiry. Data collection methods and sources included audio recordings of weekly meetings, collaborative reflections, meeting minutes, and personal journal reflection. Outcomes report on the evolution and functioning of the self-study group over an 18-month period. Principles for cultivating a community of practice are used to retroactively reflect on the successes and tensions the group experienced, group dynamics, group leadership, the nature of collaboration, individual and group learning, and strategies used to foster productive community functioning.